Incidence of saprolegniasis in fishes of Hataikheda reservoir, Bhopal - Salgotra, Vikas; Mastan, S A; Qureshi, T A (Indian Journal of Fisheries, 2011)
A total of 12 isolates of fungi were obtained from diseased fishes which belongs to four species namely Saprolegnia parasitica, Saprolegnia ferax, Saprolegnia hypogyana, Saprolegnia diclina. All these fungi were isolated from four different species of fishes viz. Channa gachua, Channa straitus, Channa punctatus, Clarias batrachus. The parasitic ability of all the twelve fungi was confirmed by conducting pathogenicity tests under laboratory conditions using healthy fishes of the same species. All the species of fungi were found to be pathogenic to fish. But Saprolegnia parasitica was more virulent showing infection within eight hours.